(3GdJMaI GdSYOjI aj TQM cdjGJ GdbGfhfs - (3bWH GdOjf eMehO Hf eSYhO Hf eUdMs; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3bGd GdTjN QMeg Gddg (B: (3GdJYdje GdSGOS Ledg , haUd GdLedI ai Gdbhi , hgj SJI aUhd , GdaUd GdChd efgG Ci ef GdLedI s
(3BNQgG (B:s
(3hEPG CQOJ Cf JYQa gPG YjGfkG aVY YTQI SQL eJbGQHI aEfc JLO GdVhA YfO GdSQGL GdhSW CcKQ cKjQkG ef GdPi YfO GdWQa , hdGjNai HYO GdEWdGY Ydi eG PcQfG hGddg CYde s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1312s
Keywords: (3GdWHs